Preparation and characterization of biodegradable poly lactid acid (PLA) composites with oil palm empty fruit bunch (EFB) fiber - Abu Kashem Moshiul, Mohammad Alam (2012)
Application of natural fibers as reinforcing material of polymer matrix is the prime attention in this research.Oil palm empty fruit bunch(EFB)fiber has been considered as reinforcing material of Poly lactic acid (PLA) for preparation of EFB/PLA biocomposites.The limitation in the broad use of EFB fiber in PLA matrix is poor compatibility between fibers and matrix due to presence of non cellulosic components and the hydroxyl groups of cellulose.Moreover,the hydroxyl groups form hydrogen bonds inside the macromolecule itself (intra-molecular) and also with hydroxyl groups from moist air that restrict the fiber matrix adhesion and also bring about dimensional changes in the fiber. These limitations has been successfully overcome by removing the non cellulosic components,altering the fiber surface,through conventional alkali (ALK)and non conventional ultrasound (ULS) pre-treatment methods.The Pre-treatment were conducted with variation of sodium hydroxide (NaOH) concentration, soaking or exposing time and treatment temperature.Fiber characterization was done by the single fiber strength,FTIR spectrum,SEM and TGA-DTG thermal analysis.The ULS EFB fiber was given best properties compare to ALK EFB fiber at mild treatment conditions.The treatment parameters were optimized on the basis of that treated EFB/PLA composites mechanical properties and by using Design Expert Software. Optimization of fiber loading was carried out by 10 wt%,20wt%,30 wt% and 40wt% raw EFB fiber,composite was prepared by extrusion with PLA followed by injection molding.The composites properties were examined by mechanical tests such as tensile strength(TS),tensile modulus TM),elongation at break (EB) and impact strength (IS). It was found that 30wt% EFB fiber incorporated composite represented good TS,TM,EB and IS. By considering these mechanical properties,30wt% EFB was considered as optimum loading in EFB/PLA composite. Beside this comparative analysis was done for 30wt% EFB fiber incorporated raw EFB/PLA, ALKEFB/PLA and ULSEFB/PLA composites.This comparison was carried out by the analysis of melt flow index (MFI),mechanical properties (TS,TM,EB,IS), kinetic property (activation energy,Ea)by TGA-DTG data and crystallinity index (IDSC)by DSC thermograms.The ULSEFB/PLA composite was shown better properties,such as higher MFI (3.55 g/10min), mechanical strength(TS= 63MPa, TM=2468 MPa, IS=18.67 J/m2), crystallinity index (IDSC=43.12) and lower activation energy (Ea=69.73 kJ/mol), compare to ALKEFB/PLA composite. Moreover,these properties were obtained when the ULSEFB fiber was treated at lower NaOH concentration(3 wt%) and treatment temperature (800C) at 90 minutes exposing time.The ULSEFB/PLA composite properties were increased by treating that ULSEFB fiber with HBPE as coupling agent in ULSEFB/HBPE/PLA composite.It shows highest MFI(4.15 g/10min) and mechanical properties (TS=66.78 MPa, TM=2629MPa, IS=19.33),greater thermal stability, highest crystallinity index (IDSC=45.13)nd lowest activation energy (Ea=67.89 kJ/mol) among all composites.